Short cervix and use of cervical pessary for preventing preterm birth in singleton and twin pregnancies: a systematic review and meta-analysis - Santos, Ana Clara Felix de Farias; Pimenta, Nicole Dos Santos; Pereira, Ana Gabriela Alves [UNESP]; Molino, Gabriela Oliveira Gonçalves; Dias, Maírla Marina Ferreira; da Silva, Pedro Henrique Costa Matos (Federação das Associações de Ginecologia e Obstetrícia, 2025)
Objective: Preterm birth remains a significant contributor to neonatal morbidity and mortality. The use of cervical pessaries as an intervention for preventing preterm delivery in women with a short cervix has been a subject of interest. We evaluated the effectiveness of cervical pessary compared to standard care in preventing preterm delivery in women with a short cervix. Data source: Databases were systematically searched in PubMed, Cochrane, and Embase databases in December 2023. Study selection: Randomized clinical trials with the outcomes of interest were included. Data collect: We computed risk ratios for binary endpoints, with 95% confidence intervals. Heterogeneity was assessed using I2 statistics. Data were analyzed using R software (version 4.3.0). The primary outcomes of interest were preterm delivery before 37 weeks, and preterm delivery before 34 weeks. Data synthesis: Seventeen studies with 5,704 patients were included. The use of cervical pessary was associated with a decreased risk of preterm delivery before 37 (RR 0.88; 95% CI 0.81-0.96) and 34 weeks (RR 0.79; 95% CI 0.63-0.99) of gestation in twin pregnancies as compared to standard care without progesterone. There were no significant differences in preterm delivery in singleton pregnancy, neonatal outcomes, preterm premature rupture of the membranes or chorioamnionitis. Conclusion: The use of cervical pessary was associated with a significant reduction in preterm delivery at 34 and 37 weeks of gestation in twin pregnancies among patients with a short cervix compared to no treatment. No significant difference was found in singleton pregnancies or maternal outcomes.
Keywords: Cervical length measurement; Pessaries; Progesterone, Premature birth; Short cervix